Analisis Peran Gender dalam Komunikasi Keluarga di Masyarakat Kota Binjai: Sebuah Pendekatan Studi Kasus - Hasibuan, Hawa Shabira; Deni, Indira Fatra (JOM, 2024)
Gender inequality is still an issue that is discussed, and its handling needs awareness from various parties, both from the government, society, and the family. The practice of gender equality in the family is still an interesting issue to be studied. excessive gender equality is feared to threaten the integrity of the family. This research aims to find out how people perceive gender equality in the family. The research method used is qualitative method. The results showed that the perception of the people of Binjai City, especially the South Binjai sub-district, Binjai Estate sub-district, neighborhood IX, is that there are still those who do not understand the term gender equality, but it has been widely practiced and accepted by the community. This is evidenced by the fulfillment of children's equal rights in the field of education, the division of domestic duties in the family equally by boys and girls, the freedom to make choices and express opinions, and freedom in making decisions in the family. In short, gender equality in the family is considered good by society as long as it does not conflict with human nature and religious values prevailing in society that prevail in society.